2010
DOI: 10.1182/blood-2009-12-255943
|View full text |Cite
|
Sign up to set email alerts
|

Identification during the follow-up of time-dependent prognostic factors for the competing risks of death and blast phase in primary myelofibrosis: a study of 172 patients

Abstract: The median survival of patients with primary myelofibrosis ranges from 3.5 to 5.5 years, and most patients die from cause related to the disease, including blast phase (BP, in 5%-30% of cases).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…More recently, dynamic prognostic models able to assess patient prognosis at different times during the course of disease have been proposed by different groups. 16,17 The one published by Morel et al 16 on behalf of the International Working Group for Myeloproliferative Neoplasms Research and Treatment was based on data available for 525 primary myelofibrosis patients and showed that the development of leukocytosis (425 Â 10 9 ) independently predicts poor survival. However, WBC differential counts values were not reported in the study.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, dynamic prognostic models able to assess patient prognosis at different times during the course of disease have been proposed by different groups. 16,17 The one published by Morel et al 16 on behalf of the International Working Group for Myeloproliferative Neoplasms Research and Treatment was based on data available for 525 primary myelofibrosis patients and showed that the development of leukocytosis (425 Â 10 9 ) independently predicts poor survival. However, WBC differential counts values were not reported in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Such an association has also been reported in PMF. [10][11][12][13] With regard to the poor prognostic significance of being on hydroxycarbamide at MF diagnosis, we think that some kind of selection bias may be operating here. Indeed, hydroxycarbamide is usually indicated in older patients and in those with more marked myeloproliferative features, and this may have contributed to blur the prognostic significance of such features.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 98%
“…2 Several models have been developed to predict survival in PMF. [3][4][5] Concerning BP occurrence, leukocyte count more than 30 ϫ 10 9 /L, 5 blast cell count more than 10%, 6 platelet count below 50 ϫ 10 9 /L, 6 red blood cell transfusion dependency, 7 selected cytogenetic abnormalities, 6,8 low JAK2(V617F) allele burden 9 have been reported to shorten BP-free survival.The International Working Group on Myeloproliferative Neoplasms Research and Treatment (IWG-MRT) has recently developed a time-dependent prognostic model, named Dynamic International Prognostic Scoring System (DIPSS) to predict survival anytime in patients with PMF. 10 This model includes age older than 65 years, hemoglobin level lower than 10 g/dL, white blood cell count more than 25 ϫ 10 9 /L, peripheral blood blasts equal to or higher than 1%, and constitutional symptoms.…”
mentioning
confidence: 99%
“…2 Several models have been developed to predict survival in PMF. [3][4][5] Concerning BP occurrence, leukocyte count more than 30 ϫ 10 9 /L, 5 blast cell count more than 10%, 6 platelet count below 50 ϫ 10 9 /L, 6 red blood cell transfusion dependency, 7 selected cytogenetic abnormalities, 6,8 low JAK2(V617F) allele burden 9 have been reported to shorten BP-free survival.…”
mentioning
confidence: 99%